Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1524/ract.2012.1908
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of C5-BTBP in cyclohexanone irradiated in the absence and presence of an aqueous phase

Abstract: Spent nuclear fuel contains many highly radioactive species; hence solvents used in reprocessing will be subjected to radiolysis. In this study, solvents containing one of the BTBP molecules intended for the separation of trivalent actinides and lanthanides, the so called C5-BTBP, have been subjected to radiolysis and hydrolysis. We present here that this compound shows a dramatic decrease in both distribution ratios and separation factor when irradiated with higher doses up to 50 kGy; particularly in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…158 Finally, the radiolytic and oxdiative stability of C5-BTBP in cyclohexanone in the presence of an aqueous phase was studied. 160 Stability versus oxidative degradation was tested by contacting solutions of C5-BTBP in cyclohexanone with water or with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; radiolytic stability was tested on (a) pure organic phases; (b) organic phases pre-equilibrated with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; and (c) organic phases in contact with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 . The results were evaluated by determining D Am(III) and D Eu(III) and by measuring C5-BTBP and degradation product concentrations using HPLC and LC-MS. After 330 h in contact with water, 2 mmol/L of initially 5 mmol/L C5-BTBP in cyclohexanone remained; the same decrease was observed after 200 h when in contact with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 .…”
Section: C5-btbpmentioning
confidence: 89%
See 1 more Smart Citation
“…158 Finally, the radiolytic and oxdiative stability of C5-BTBP in cyclohexanone in the presence of an aqueous phase was studied. 160 Stability versus oxidative degradation was tested by contacting solutions of C5-BTBP in cyclohexanone with water or with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; radiolytic stability was tested on (a) pure organic phases; (b) organic phases pre-equilibrated with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; and (c) organic phases in contact with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 . The results were evaluated by determining D Am(III) and D Eu(III) and by measuring C5-BTBP and degradation product concentrations using HPLC and LC-MS. After 330 h in contact with water, 2 mmol/L of initially 5 mmol/L C5-BTBP in cyclohexanone remained; the same decrease was observed after 200 h when in contact with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 .…”
Section: C5-btbpmentioning
confidence: 89%
“…Finally, the radiolytic and oxdiative stability of C5-BTBP in cyclohexanone in the presence of an aqueous phase was studied . Stability versus oxidative degradation was tested by contacting solutions of C5-BTBP in cyclohexanone with water or with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; radiolytic stability was tested on (a) pure organic phases; (b) organic phases pre-equilibrated with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 ; and (c) organic phases in contact with 0.01 mol/L HNO 3 + 0.99 mol/L NaNO 3 .…”
Section: Lipophilic Bistriazinyl Bipyridines (Btbp)mentioning
confidence: 98%
“…The radiation stability of different variations of the r-SANEX system has been widely studied in the last 2 decades. This research focused mainly on the molecules CyMe 4 -BTP, C5-BTBP, CyMe 4 -BTBP, and CyMe 4 -BTPhen in different types of diluents, such as octan-1-ol or its mixtures, FS-13, cyclohexanone, or its derivatives. , Each solvent behaved differently under irradiation. First, a difference was found in the distribution ratio ( D -values) when only the organic phase was irradiated and when the organic phase was irradiated in contact with the aqueous phase .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an aqueous phase during irradiation of C5-BTBP in cyclohexanone was studied by Fermvik et al [19]. It was found that in the presence of an aqueous phase the degradation of the extractant increased.…”
Section: Introductionmentioning
confidence: 99%